Digital storytelling: pre-service English teachers' experiences, difficulties and solutions - Nuroh, Ermawati Zulikhatin; Retnaningdyah, Pratiwi; Munir, Ahmad (Intelektual Pustaka Media Utama, 2025)
This study aimed to investigate the impact of digital storytelling on the teaching practicum experiences of pre-service English teachers (PSET) and to delve into the challenges they encountered in creating digital storytelling, along with the strategies used to overcome these challenges. This study provided deeper understanding of the impact of digital storytelling on the learning and teaching experiences of PSET. Moreover, it provided information to face obstacles in the digital storytelling creation process. A total of 30 PSET, comprising 13 males and 17 females, engaged in their sixth-semester teaching practicum, participated in this study. Self-reflection and semi-structured interviews were conducted to collect the data. The researcher applied thematic analysis to analyze the data obtained. The findings of this study revealed that the implementation of digital storytelling yielded positive experiences for PSET, encompassing enhancements in pedagogical approaches, self-development, and technology integration into the teaching-learning process. PSET encountered various difficulties in creating digital storytelling, including seamless integration of movement, audio, images, and animations within the narrative, crafting engaging animations and narratives, and proficiency in using diverse editing applications. Moreover, the challenges encompassed collecting and curating appropriate materials and organizing a coherent storyline aligning with the lesson plans and real-world contexts. Nevertheless, PSET proposed solutions to overcome those difficulties.